2013
DOI: 10.1007/s13277-013-0961-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor in lung cancer 1 (TSLC1), a novel tumor suppressor gene, is implicated in the regulation of proliferation, invasion, cell cycle, apoptosis, and tumorigenicity in cutaneous squamous cell carcinoma

Abstract: Tumor suppressor in lung cancer 1 (TSLC1) is tightly implicated in a variety of biological processes and plays critical roles in tumor development and progression. However, the roles of TSLC1 in cutaneous squamous cell carcinoma (CSCC) remain to be unraveled. Here, we reported the TSLC1 gene that was significantly downregulated in CSCC tissues and cells, and survival times of patients with TSLC1 at a low level were markedly lower than that at a high level (P = 0.0070). A stepwise investigation demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…In Kaplan-Meier survival analysis, we found that the overall survival (OS) of CADM1/TSLC1 negative group was significantly lower than that in CADM1/TSLC1 positive group, which was consistent with the results in other studies of esophageal squamous cell carcinoma (ESCC) [ 14 ], as well as skin squamous cell carcinoma [ 20 ], laryngeal carcinoma [ 13 ], meningioma [ 21 ], breast cancer [ 22 ], nasopharyngeal carcinoma (NPC) [ 23 ], lung adenocarcinoma [ 9 ], and colon cancer [ 12 ]. Furthermore, our results suggested that CADM1/TSLC1 negative expression was associated with shorter disease-free survival (DFS) and accordingly might predict early relapse of patients with ESCC after surgery.…”
Section: Discussionsupporting
confidence: 90%
“…In Kaplan-Meier survival analysis, we found that the overall survival (OS) of CADM1/TSLC1 negative group was significantly lower than that in CADM1/TSLC1 positive group, which was consistent with the results in other studies of esophageal squamous cell carcinoma (ESCC) [ 14 ], as well as skin squamous cell carcinoma [ 20 ], laryngeal carcinoma [ 13 ], meningioma [ 21 ], breast cancer [ 22 ], nasopharyngeal carcinoma (NPC) [ 23 ], lung adenocarcinoma [ 9 ], and colon cancer [ 12 ]. Furthermore, our results suggested that CADM1/TSLC1 negative expression was associated with shorter disease-free survival (DFS) and accordingly might predict early relapse of patients with ESCC after surgery.…”
Section: Discussionsupporting
confidence: 90%
“…TSLC1 has been reported as a tumor suppressor gene that is involved in multiple cellular processes such as cell proliferation, differentiation, migration, and invasion [26, 27]. Tsujiuchi et al reported that in HCC induced by N-nitrosodiethylamine, the 5’ upstream region of TSLC1 was methylated and its expression was reduced [18].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in HRAS, KRAS, and EGFR have also been detected in cSCC, emphasizing the role of EGFR and extracellular signal-regulated kinase 1/2 (ERK1/2) signaling in development of cSCC (Ratushny et al, 2012). Recently, previously unreported markers for progression of cSCC have been identified and characterized (Farshchian et al, 2011(Farshchian et al, , 2015Liu et al, 2013;Riihilä et al, 2014Riihilä et al, , 2015Trimmer et al, 2012), but understanding of the molecular basis of cSCC progression from premalignant lesion (actinic keratosis, AK) to cSCC in situ (cSCCIS) and eventually to invasive cSCC remains incomplete.…”
Section: Introductionmentioning
confidence: 99%